Implementation of Wet Coffee Peeling Machine In Barus Julu Village Kecamatan Barus Jahe Karo District - Timbangen Sembiring; Ferry Rahmat A. Bukit; Ivo Andika Hasugian; Erna Frida (Talenta Publisher, 2020)
The application of the wet coffee peeler has been implemented in Barusjulu Village, Barusjahe District, Karo Regency, the method used is to make and assemble a wet coffee peeler with a machine, so that coffee peeling can be done quickly. Monitoring is carried out to ensure that farmers can use their tools and functions properly. From the results of using a wet coffee peeler in Barusjulu Village, it can be concluded that the performance of the tool works well, efficiently and coffee farmers are helped by the wet coffee peeler.